2021
DOI: 10.1371/journal.pone.0255641
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal parasitic infections and associated factors among street dwellers and prison inmates: A systematic review and meta-analysis

Abstract: Background Intestinal parasitic infections are closely associated with low household income, poor personal and environmental sanitation, and overcrowding, limited access to clean water, tropical climate and low altitude. Street dwellers and prisoners are forced to live in deprived situations characterized by inadequate facilities. Therefore, this study aimed to estimate the pooled prevalence and associated factors of intestinal parasitic infections among street dwellers and prison inmates. Method Study searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
0
9
1
Order By: Relevance
“…In the present study participants who eat unwashed raw fruits/vegetables were 3.4 times at higher risk of IPIs compared with those who eat washed raw fruits/vegetables (adjusted OR: 3.4, 95% CI: 1.87 to 15.13, p = 0.004). Similarly, a study conducted in Ethiopia and neighboring country showed habit of eating unwashed fruit or raw vegetable had shown a strong association with parasitic infection [ 4 , 47 ]. This finding highlights unwashed fruit and vegetables as a potential source of IPIs infection due to the high rate of contamination with Intestinal parasite [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study participants who eat unwashed raw fruits/vegetables were 3.4 times at higher risk of IPIs compared with those who eat washed raw fruits/vegetables (adjusted OR: 3.4, 95% CI: 1.87 to 15.13, p = 0.004). Similarly, a study conducted in Ethiopia and neighboring country showed habit of eating unwashed fruit or raw vegetable had shown a strong association with parasitic infection [ 4 , 47 ]. This finding highlights unwashed fruit and vegetables as a potential source of IPIs infection due to the high rate of contamination with Intestinal parasite [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two authors, AS and MG, used this scale independently to assess the methodological quality, scale (comparability), and outcome of each study, and if there was any disagreement between them, a third author opinion was used to make the agreement, and a score of 7 out of 10 was considered as the good quality of the studies. In this research, studies that gain scores seven and higher were included [15], because different methods and scales were used in studies to report the results, and there was a high heterogeneity, so it was not possible to perform meta-analysis on them, so we used narrative synthesis to summarize the research findings. A researcher-designed checklist was used to record the required data including title, first author, location, the total number of subjects, number of subjects by gender, and study findings.…”
Section: Qualification and Data Extractionmentioning
confidence: 99%
“…Nematodes are largely responsible for these diseases, including Ascaris lumbricoides , Trichiuris trichiuria , Ancylostoma duodenale and Strongyloides stercoralis [ 1 , 2 , 3 , 4 , 5 , 6 ]. Diseases caused by intestinal nematodes can cause, among others, abdominal pain, dehydration, weight loss, anemia, intestinal obstruction, disorders of mental and physical development, malabsorption, inflammation and in severe cases, if left untreated, these can even lead to death [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%